Hyperspectral cathodoluminescence, trace element, and U-Pb geochronological characterization of apatite from the Ernest Henry iron oxide copper-gold (IOCG) deposit, Cloncurry district, Queensland - Steadman, Jeffrey A.; Goemann, Karsten; Thompson, Jay M.; MacRae, Colin M.; Belousov, Ivan; Hohl, Max (Frontiers in Earth Science, 2022)
Hyperspectral cathodoluminescent (CL), geochemical, and geochronological characterization of a series of apatite-bearing samples from within and around the Ernest Henry IOCG deposit, NW Queensland, Australia, have revealed complex mineral parageneses and a spectrum of U-Pb ages that point to the effects of multiple geological processes. No two samples are identical, either in geochemistry or texture, despite their relative proximity to one another (all samples within 5 km from Ernest Henry). Hyperspectral CL maps reveal diverse internal textures and emissions ranging from near infrared (NIR) to near ultraviolet (UV) with a complex series of spectra in all samples, requiring the fitting more than 40 individual peaks (both sharp and broad) to capture the observed variability. Imaging analyses via LA-ICPMS show that apatite from the Ernest Henry district is enriched above background in a variety of trace elements, including Na, Mg, Al, Si, V, Mn, As, Sr, Y, the rare earth elements (REEs), Pb, Th, and U. Samples outside the ore zone display chondrite-normalized REE profiles that are consistent with either a magmatic or hydrothermal origin, whereas ore zone apatite exhibits profiles that are decidedly hydrothermal in nature. Moreover, specific zones within ore zone apatite grains are very As-rich (up to 7 wt. % As2O5), and the effect of such high As on the hyperspectral CL signature of these zones is a pronounced dampening of CL emission, regardless of REE concentrations. Uranium-Pb dating of the same samples (via LA-ICPMS) has yielded a diverse array of overlapping Mesoproterozoic ages ranging from 1580 ± 34 Ma to 1533 ± 61 Ma. These results correlate to published ages that constrain hydrothermal alteration in the Ernest Henry area, both before and during Cu-Au mineralization. Collectively, these data highlight the complexity of apatite studies at Ernest Henry, the broader Cloncurry district, and probably analogous terranes elsewhere. A combination of micro-scale methods such as those used in this study are shown to be essential for accurately deciphering geological information contained within petrogenetic indicator minerals.